2016
DOI: 10.1002/mds.26702
|View full text |Cite
|
Sign up to set email alerts
|

Similar α‐Synuclein staining in the colon mucosa in patients with Parkinson's disease and controls

Abstract: Conventional immunohistochemistry α-synuclein staining in colon mucosal biopsies cannot serve as a biomarker of idiopathic PD. These findings do not contradict the assumption of disease starting in the colon, and a colon segment-specific risk for disease initiation can still be hypothesized. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…The deposition of α-syn within the colon can help to distinguish PD patients from controls [1013]. Nevertheless, when assessed with conventional immunohistochemistry, its diagnostic value as a biomarker has not been finally confirmed as α-syn staining in colonic mucosa was likewise found in PD patients and controls [14], which not necessarily refutes the concept of an intestinal origin of PD pathogenesis. Thus, additional yet unidentified factors beyond α-syn must be involved in the presumed PD disease process.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of α-syn within the colon can help to distinguish PD patients from controls [1013]. Nevertheless, when assessed with conventional immunohistochemistry, its diagnostic value as a biomarker has not been finally confirmed as α-syn staining in colonic mucosa was likewise found in PD patients and controls [14], which not necessarily refutes the concept of an intestinal origin of PD pathogenesis. Thus, additional yet unidentified factors beyond α-syn must be involved in the presumed PD disease process.…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal tract is the most studied in vivo tissue for α-syn aggregates to date. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Previous autopsy-based studies reported relatively high prevalence of abnormal α-syn deposits in the gastrointestinal tract among peripheral tissues. 3 Within the gastrointestinal tract, abnormal α-syn deposits have been shown to be concentrated on the Meissner's submucosal plexus and Auerbach's myenteric plexus, 3,48 and there is a rostrocaudal gradient in terms of the severity of α-syn deposition with the esophagus being most severely involved.…”
Section: Discussionmentioning
confidence: 99%
“…Improved quantification of aSyn staining could also benefit sensitivity and specificity. To date, studies have mostly used qualitative assessment of sections to define pathology, and only a few studies have attempted quantification with semiquantitative grading scales to measure the severity of staining [14,20,39]. Virtual microscopy and whole-slide imaging could allow a more robust quantitative analysis of enteric aSyn and potentially facilitate definition of reliable cut-off scores to distinguish PD patients from controls.…”
Section: Discussionmentioning
confidence: 99%